(untitled) (Journal of Preventive and Social Medicine, 2020)
Background: Bangladesh bears the double burden of extreme exposure and high vulnerability to both natural and man-made disasters. In 2017, an enormous influx of Forcibly Displaced Myanmar Nationals from Myanmar to Bangladesh created massive humanitarian crisis due to geopolitical conflicts. Objective: The objective of this study was to assess the FDMN’s health situation and to work with the district health office facing the emergency. Another objective was to introduce a proper Incident Command System (ICS) approach in order to achieve system efficiencies and improve management capabilities of the district health office. Materials and Methods: This qualitative, exploratory study was conducted at three Upazilas and two disaster prone coastal civil surgeon offices in Bangladesh over a period of one year from May, 2017 to April, 2018. The target population of the study was FDMN’s, local inhabitants, health care providers, public health managers and administrators at different level. Using non-probability purposive sampling method as data collection procedure, 50 semi-structured interviews were carried out. Results: A rapid field assessment was done followed by detailed field assessment. In rapid field assessment it was observed that gaps in proper leadership created confusion and for that some participants were overlooked, while others were underutilized. There was gap in coordination between different actors in the field. It was observed that in crisis situation, challenges associated with coordination and delegations were almost similar. Interview was taken based on concepts from political and social science approaches. Under each approach emergency health management issues, gaps and constrain were discussed along with proposed solutions. In order to conduct a detailed field assessment incident command system approach were broken down to five major categories. Two ICS orientation workshop were done in Cox’s Bazar and Chittagong civil surgeon office. It was evident that CS offices would not have the entire workforce as ICS structure demand but identifying existing stuffs that could fill in all those roles in ICS structure with how to work and go in operation was done. Conclusion: The study advocates that with limited resources utmost priority should be given to train the existing workforce for emergency preparedness, planning and response. Evidence-based incident command system deployment would be beneficial for health emergency management for vulnerable people in Bangladesh. JOPSOM 2019; 38(2): 53-62